An effective key distribution for secure internet pay‐TV using access key hierarchies. Issue 18 (27th October 2016) - Vijayakumar, Pandi; Naresh, Ramu; Islam, SK Hafizul; Deborah, Lazarus Jegatha
Abstract: Distribution of keys in a Conditional Access System takes long computation time because a huge number of keys is to be updated if any user leaves or joins the system. Moreover, it is necessary to send the keys securely to the authorized members. Thus, an effective key distribution protocol for Internet Pay‐TV system is designed in this article to lower the computation time taken to compute the re‐keying information. In the proposed protocol, when the Service Provider needs to refresh a new shared secret key and link values, only a few key updating operations are needed, and they can be achieved using four primary operations, namely, hash function, addition, subtraction, and multiplication. From the experimental results, we perceive that the proposed approach takes less computation cost, communication cost and storage cost compared with other competitive protocols available in the literature. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : 1) We proposed a novel key distribution protocol for Internet Pay‐TV system. 2) The simulation results showed that our protocol takes less computation, communication, and storage costs compared with other protocols. 3) Our protocol provides forward and backward securities, and resilience against collusion attack